PENGENDALIAN KUALITAS PROSES PRODUKSI KEMASAN PLASTIK STANDING POUCHES DI PT. EPAC FLEXIBLES INDONESIA - Audrey Marisi Caroline; Carla Olyvia Doaly (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
PT. ePac Flexibles Indonesia is the first factory in Asia. PT. ePac Flexibles Indonesia is also a digital flexible packaging company that was founded in accordance with its mission, which is to help brands of all sizes be more competitive with packaging forms such as standing pouches, lay flat pouches, and roll stock. The company is also bringing the latest developments in digital printing technology to provide its customers a quick and easy way to purchase flexible packaging with customizable printouts. This company uses a check sheet to record defective products. With this check sheet, you will be able to find out the causes of product defects. Therefore, with this observation, it will be known the type of product defect that most often occurs in the production process of standing pouches plastic packaging. From observations made from August to September 2021, these data were obtained and the defect data will be processed using several tools, namely P control charts, Pareto diagrams, fishbone diagrams, and 5 why analysis. From the results of data processing, it is found that the types of defects that often occur are WIP connections, untidy cuts, and fibrous edges. These factors, namely human factors due to lack of attention to products, method factors due to lack of inspection on the roll before proceeding to the production process, machine factors due to lack of checking on machines, especially cutting knives, and environmental factors because the air in the production process room is still quite hot.